Light-mediated multi-target protein degradation using arylazopyrazole photoswitchable PROTACs (AP-PROTACs) - Zhang,Q; Kounde,C; Mondal,M; Zhang,L; Conole,D; De,Vita E; Fuchter,M; Tate,E (Chemical Communications, 2022)
Light-activable spatiotemporal control of PROTAC-induced protein degradation was achieved with novel arylazopyrazole photoswitchable PROTACs (AP-PROTACs). The use of a promiscuous kinase inhibitor in the design enables this unique photoswitchable PROTAC to selectively degrade four protein kinases together with on/off optical control using different wavelengths of light.